Cross-talks between perivascular adipose tissue and neighbors: multifaceted nature of nereids - Li, Yujuan; Chen, Zhang; Xiao, Ying; Li, Xinzhi (Frontiers in Pharmacology, 2024)
Perivascular adipose tissue (PVAT) is a unique fat depot surrounding blood vessels and plays a vital role in the progression of vascular remodeling and dysfunction. PVAT exhibits remarkable differences in structure, phenotype, origin, and secretome across anatomical locations. The proximity of PVAT to neighboring vascular beds favors a niche for bidirectional communication between adipocytes and vascular smooth muscle cells, endothelial cells, and immune cells. In this review, we update our understanding of PVAT’s regional differences and provide a comprehensive exploration of how these differences impact cross-talks between PVAT and the vascular wall. Different PVAT depots show different degrees of vasoprotective function and resilience to pathological changes such as obesity and vasculopathies, shaping multifaceted interactions between PVAT depots and adjacent vasculatures. The depot-specific resilience may lead to innovative strategies to manage cardiometabolic disorders.